Interpreting animal behaviors – A cautionary note about swaying in phasmids - Tan, Eunice J.; Elgar, Mark A.; Bian, Xue; Peters, Richard A. (Frontiers in Ecology and Evolution, 2023)
Diverse animals from snakes, spiders to phasmids sway in response to abiotic and biotic factors. Recent research on swaying in phasmids suggest they may adopt distinctive swaying to reduce detection from predators. This view was recently challenged, by interpreting swaying behavior as serving a balancing function related to postural sway and not a form of anti-predator behavior. We dispute this interpretation as the reanalysis of data for balance was based on an erroneous perception of the upright posture of the insects, contrary to the initial study and natural history observations. We present observations collected from four species of more than 300 phasmids over a three-day period and show that the insects seldom adopt an upright posture (4% of observations). While we appreciate that attempts to reinterpret data form a central role of the scientific method, we urge caution when inferring biological function without an accurate knowledge of the species’ natural history. Investigations of signals in motion require great care to ensure they are interpreted in a natural environment and context.